2022
DOI: 10.5829/ije.2022.35.12c.02
|View full text |Cite
|
Sign up to set email alerts
|

Installation Depth and Incident Wave Height Effect on Hydrodynamic Performance of a Flap Type Wave Energy Converter: Experimental Analysis

Abstract: The effect of installation depth and height of the incident wave on the hydrodynamic and economic performance of an oscillating wave surge converter (OWSC) wave energy converter is crucial. In this study, an OWSC by considering 1:8 scale has been studied under Caspian Sea wave conditions for 8 water depths from the semi-submerged to fully submerged. The study has been conducted to achieve the best draft ratio and evaluate the systems performance imposed to Caspian waves condition by experimantal method.The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
0
0
Order By: Relevance
“…These reactive controllers take into account the power losses during the conversion from mechanical to electrical energy (2). Also, the authors showed the hydrodynamic and economic performance of an oscillating wave surge energy converter is significantly influenced by the installation depth and height of the incident wave (3). In (4), the authors introduced a novel configuration for a linear permanent magnet Vernier machine, specifically tailored for harnessing wave energy and enhancing the operational efficiency of the existing Vernier machine prototype.…”
Section: Introductionmentioning
confidence: 99%
“…These reactive controllers take into account the power losses during the conversion from mechanical to electrical energy (2). Also, the authors showed the hydrodynamic and economic performance of an oscillating wave surge energy converter is significantly influenced by the installation depth and height of the incident wave (3). In (4), the authors introduced a novel configuration for a linear permanent magnet Vernier machine, specifically tailored for harnessing wave energy and enhancing the operational efficiency of the existing Vernier machine prototype.…”
Section: Introductionmentioning
confidence: 99%